Design and Integration of Valves Controller for Drone Monitored Solar Irrigation System - Alnaimi F.B.I.; Rosli M.L.S.; Vasu R.; Mahdi M.N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Citrus fruits; Controllers; Crops; Drones; Microcontrollers; Solar energy; Solenoid valves; Water supply; Control valves; Design and integrations; Drone; Irrigation systems; Lemon myrtles; Microcontroller; Solar; Solar irrigations; Valve controllers; Water use; Irrigation